Evaluating PPGIS Usability in a Multi-National Field Study Combining Qualitative Surveys and Eye-Tracking. (3rd April 2021) - Bartling, Mona; Resch, Bernd; Trösterer, Sandra; Eitzinger, Anton
ABSTRACT: For designing qualitative interfaces for Public Participatory Geographic Information Systems (PPGIS), the user and use case should be clearly defined. However, PPGIS users may differ significantly, e.g. regarding their cultural background, IT-literacy, or interests. Studies examining varying user types and their impact on PPGIS usability are, however, lacking. In this paper, we analyse the user spectrum through conducting a usability study with 73 participants located in Colombia, Uganda and Austria. We combined a qualitative survey (conducted in all three countries) with an eye-tracking based survey (conducted only in Austria). Most of the usability issues arose due to inexperience in using interactive maps or applications other than social media. Based on the findings, we explored which user context information had an impact on which usability problem. With this, we designed an adaptation gradient that can be used for future research on developing adaptive PPGIS interfaces.